1998
DOI: 10.1149/1.1838461
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Superior Water Blocking Ability of Electron Cyclotron Resonance‐Plasma SiO2 Film

Abstract: The superior water blocking ability of electron cyclotron resonance (ECR)-plasma 5i02 film has been investigated. We compared this film to normally used dielectric films in the field of multilevel interconnection technology, such as a Sill4plasma 5i02 film and a tetraethoxysilane (TEOS)-plasma 5i02 film by the pressure cooker test. The structural difference between these films was investigated by Fourier transform infrared spectroscopy and Raman spectroscopy. We found that the improved performance was due to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…In addition, the low dielectric constant ͑low-k͒ materials are also proposed for decreasing the parasitical capacitor for future integrated circuit ͑IC͒ applications. [3][4][5][6][7][8][9] One of the promising low-k dielectrics, a spin-on deposition hybrid organic siloxane polymer ͑HOSP͒ is a strong candidate. The HOSP is derivative of SiO 2 , in which one of the four oxygen atoms bonded to every silicon atom is replaced by hydrogen and methyl groups.…”
mentioning
confidence: 99%
“…In addition, the low dielectric constant ͑low-k͒ materials are also proposed for decreasing the parasitical capacitor for future integrated circuit ͑IC͒ applications. [3][4][5][6][7][8][9] One of the promising low-k dielectrics, a spin-on deposition hybrid organic siloxane polymer ͑HOSP͒ is a strong candidate. The HOSP is derivative of SiO 2 , in which one of the four oxygen atoms bonded to every silicon atom is replaced by hydrogen and methyl groups.…”
mentioning
confidence: 99%
“…Okuda et al reported that the H atom of Si-H bond can be broken by OH-containing molecules. 12 Therefore, we hydrolyzed the sample in water to break the Si-H bond according to the following reaction:…”
Section: Resultsmentioning
confidence: 99%
“…FT-IR spectroscopy was used to roughly study the content of H 2 O and the existence of Si-OH (3700 and 960 cm À1 ) and H-OH bonds (3400-3200 cm À1 ). [15][16][17] The FT-IR spectra of the film are shown in Figs. 7(a) and 7(b).…”
Section: H 2 O Contentmentioning
confidence: 99%